Sulfuric acid resistance of one-part alkali-activated mortars. (July 2018) - Sturm, P.; Gluth, G.J.G.; Jäger, C.; Brouwers, H.J.H.; Kühne, H.-C.
Abstract: One-part alkali-activated (geopolymer) mortars based on three different silica-rich starting materials and sodium aluminate, with and without ground granulated blast furnace slag (GGBFS) addition, were tested regarding sulfuric acid resistance according to DIN 19573:2016-03 (70 days at pH = 1). Corresponding pastes were characterized by XRD, SEM, chemical analysis, 29 Si MAS NMR and 1 H- 29 Si CPMAS NMR after water storage and after acid exposure. The mortars exhibited a high resistance against sulfuric acid attack, with the best ones conforming to the requirements of DIN 19573:2016-03. The analytical results showed that this was due to precipitation of silica gel at the acid-mortar interface, which formed a mechanically stable layer that protected the subjacent mortar and thus inhibited further degradation. The addition of GGBFS decreased the acid resistance via formation of expansive calcium sulfate phases.